Gulf Economic Monitor, February 2018 : Deepening Reforms - World Bank Group (World Bank, Washington, DC, 2018)
This second edition of the twice-yearly Gulf Economic Monitor describes recent economic developments, near-term prospects, and broader reform priorities in the Gulf Cooperation Council (GCC) countries (The Pulse of the Region). Regional aggregate GDP growth in 2017 weakened to just 0.5 percent, weighed down by oil production cuts and tighter fiscal policy that took a toll on non-oil growth. Prospects, however, are for a gradual strengthening, helped by the partial recovery in energy prices, the expiration of oil production cuts after 2018, and an easing of fiscal austerity. Aggregate growth in the region is expected to strengthen to 2.1 and 2.7 percent in 2018 and 2019, respectively. Risks to the outlook include potential external headwinds resulting from the tightening of monetary policy in advanced economies and/or geopolitical tensions that lead to volatility in global financial markets or commodity prices. Although fiscal and external balances are improving, the region continues to face large financing needs among both sovereigns and corporates, and thus remains vulnerable to volatility in global capital flows and the cost of funding. Finally, the reform agendas under consideration in GCC countries are necessarily complex and require considerable political resolve. The Monitor also describes how, following three years of sustained fiscal adjustments to lower oil prices, the GCC countries, led by the Kingdom of Saudi Arabia, are shifting attention towards deeper structural reforms. These are needed to breathe new life into sluggish domestic economies, create jobs for young people and strengthen private investment, to broaden the economic base and to anchor longer term fiscal sustainability. The report, however, cautions against policy complacency stemming from the recent partial recovery in oil prices that leads to loss in reform momentum. Instead, it urges countries to double down on reforms in order to secure the long term futures of their economies and their people. The final part of the report includes an analytical In Focus section that discusses the sustainability, equity, and welfare challenges confronting regional pension systems.